Fasting Serum IGFBP-1 as a Marker of Insulin Resistance in Diverse School Age Groups - Bhangoo, Amrit; Gupta, Rishi; Shelov, Steve P.; Carey, Dennis E.; Accacha, Siham; Fennoy, Ilene; Altshuler, Lisa; Lowell, Barbara; Rapaport, Robert; Rosenfeld, Warren; Speiser, Phyllis W.; Ten, Svetlana; et al. (Frontiers in Endocrinology, 2022)
Abstract Introduction: The known markers of insulin resistance in obese children are well studied. However, they require serial measurements and complicated calculations. The objective is to study IGFBP-1 and its relation other known risk measures. Materials and Methods: The study included 98 New York City school students of diverse ethnic/racial background (57 males and 41 females), 11-15 years of age. Subjects were enrolled in a cross-sectional study and anthropometric measures were collected. They underwent fasting intravenous glucose tolerance tests (IVGTT), glucose, insulin, lipids, IGFBP-1, adiponectin and inflammatory markers were collected. Results: The subjects were stratified into 3 groups based upon BMI Z-score. Out of all the subjects 65.3 % were in the Group with BMI Z-score < 1 SDS, 16.3 % subjects were in the Group with BMI Z-score of 1 to 2 SDS and 18.4 % of the subjects were in the Group with BMI Z-score of more than 2 SDS. Group with BMI Z-score more than 2 SDS had increased waist circumference (WC), body fat, increased fasting insulin and triglycerides (TG). This group had decreased levels of adiponectin, HDL and low IGFBP-1 as compared to Group with BMI < 1 SDS. Group with BMI Z-score 1 to 2 SDS had decreased level of IGFBP-1 as compared to the Group with BMI Z-score less than 1 SDS. IGFBP-1 inversely correlated with age, WC, BMI, body fat, TG, and insulin levels. IGFBP-1 positively correlated with adiponectin and HDL levels. Conclusion: IGFBP-1 in children can identify the presence of insulin resistance in the group with BMI 1 to 2 SDS, even before the known markers of insulin resistance such as elevated triglycerides and even before decreased HDL and adiponectin levels are identified.